Transpedicular Screw Fixation of Traumatic Thoracolumbar Spine Fracture Open Versus Percutaneous Technique - Jawad Jan Arif, Subhan Shahid, Tanveer Afzal, Muhammad Abubakar, Ali Irfan (Pakistan Journal of Medical & Health Sciences, 2023)
Objective: To determine meantime to return to work of patients with traumatic thoracolumbar spine fracture managed with open versus percutaneous trans-pedicular screw fixation. Materials and methods: A randomized controlled trial conducted in a joint venture of orthopedic and neurosurgeons in a private hospital of Lahore. Study was completed in six months duration from July to December 2022. 80 patients having traumatic thoracolumbar spine fractures presenting to the study hospital and falling in inclusion criteria were enrolled into this study. Two groups made containing equal number of patients in each (n=40). One group underwent open transpedicular screw fixation and other group underwent percutaneous trans-pedicular screw fixation. Monthly follow up was done and the time taken return to work (TTRW) was noted. Results: Mean age of the patients was 34.62 years. There were 40(50%) male and 40(50%) female patients in the study group (n=80). Mean time taken return to work after the surgery was 3.1±0.61 months in group-A (percutaneous screw fixation) versus 5.2±0.84 months in group-B (open screw fixation). The difference in two groups regarding TTRW was significant (p<0.005). Male and female patients showed significant difference in TTRW within group-A (p=0.021) while no significance difference found in TTRW among male and female patients within group-B (p=0.18). Duration of the procedure had significant impact on TTRW (p=0.001). Practical Implication: Percutaneous technique has been proved to be safer, quicker and minimal invasive method that should replace open technique. It is recommended to conduct comparative randomized controlled trials on larger study groups to obtain more data regarding outcomes of percutaneous versus open technique. This study helps us to understand comparatively safety, efficacy and feasibility of both techniques so that better treatment option may be used in such patients for better outcomes. Conclusion: We concluded that time taken return to work was shorter in the patients treated by percutaneous technique of transpedicular screw fixation versus those patients treated by open technique. Percutaneous technique has shorter duration of the procedure, less morbidity, early recovery and more effective. Keywords: Transpedicular screw fixation, Thoracolumbar spine fracture, Spinal cord injury, Time taken return to work